2018
DOI: 10.1039/c8ay00192h
|View full text |Cite|
|
Sign up to set email alerts
|

Correcting the effect of hematocrit in whole blood coagulation analysis on paper-based lateral flow device

Abstract: A simple method to correct the effect of hematocrit (Hct) on a paper-based lateral flow assay device that is designed to assess whole blood coagulation is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Non-specific binding by plasma constituents in such complex matrices can yield false positive or false negative results [ 96 ]. Variable hematocrit levels can impact the rate of blood flow on the assay as a higher percentage of red blood cells can result in faster coagulation and therefore less fluid movement [ 97 , 98 ]. For example, blood samples from people with anemia or who are on anticoagulants would migrate faster than those with more viscous blood which may change the binding characteristics and assay sensitivity.…”
Section: Challenges With Serology Assay Development and Implementatiomentioning
confidence: 99%
“…Non-specific binding by plasma constituents in such complex matrices can yield false positive or false negative results [ 96 ]. Variable hematocrit levels can impact the rate of blood flow on the assay as a higher percentage of red blood cells can result in faster coagulation and therefore less fluid movement [ 97 , 98 ]. For example, blood samples from people with anemia or who are on anticoagulants would migrate faster than those with more viscous blood which may change the binding characteristics and assay sensitivity.…”
Section: Challenges With Serology Assay Development and Implementatiomentioning
confidence: 99%
“…Whole blood tests are considered the “gold standard” in clinical diagnostics . Because the intense red color of hemoglobin interferes with the readout of colorimetric or optical detection-based diagnostic tests, plasma separation is a common first step to increase diagnostic test accuracy. The traditional method for separating plasma from whole blood in lab settings is centrifugation. Plasma separation in both traditional blood centrifuges and in lab-on-CD platforms , require bulky equipment, which limits their application in the point-of-care setting.…”
mentioning
confidence: 99%
“…In fact, it was found that the respective LFA proved to be slightly superior in detecting very weak or very strong coagulation as compared to CoaData 2000 Fibrintimer data. The correlation of hematocrit with that of coagulation time was, however, a factor affecting the PT results, which were further addressed and corrected by the author in the LFA device in their consequent studies [ 92 ]. The LFA device after hematocrit correction provided acceptable PT measures when compared and correlated to the results of the standard CoaguChek ® XS coagulometer.…”
Section: Point Of Care Pt/inrmentioning
confidence: 99%